KRITIK SASTRA FEMINISME RADIKAL DALAM NOVEL PEREMPUAN YANG MENUNGGU DI LORONG MENUJU LAUT KARYA DIAN PURNOMO - Tharisa Desiana Fitri; Wahyu Wibowo; Kurnia Rachmawati (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the forms of resistance of female characters in the novel Perempuan yang Menunggu di Lorong Menuju Laut by Dian Purnomo using the framework of feminism literary criticism the women as a reader with Kate Millet's radical feminism analysis theory. The researcher used a case study strategy and note-taking technique in data collection. Data analysis used descriptive qualitative techniques. The results showed that there are seven forms of resistance of female characters from Kate Millet's eight perspectives of radical feminism which include, ideological perspective, biological perspective, sociological perspective, educational and economic perspective, and psychological perspective.